PENGARUH FAKTOR INTERNAL TERHADAP KEJADIAN DERMATITIS KONTAK IRITAN (DKI) PADA NELAYAN DI DESA PADELEGEN KABUPATEN PAMEKASAN - Erwin Cahya Meilanda; Septia Dwi Cahyani; Rudy Joegijantoro (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2022)
ABSTRACT Irritant contact dermatitis is a non-immunologic reaction/skin inflammation caused by irritant substances. Factors that influence the occurrence of Irritant Contact Dermatitis, among others, work period, personal hygiene and use of Personal Protective Equipment. Complaints of Contact Dermatitis Irritants such as pain, itching, erythema, stinging, scaly and cracked skin, and thickening of the skin. This study aims to analyze the influence of internal factors on the incidence of Irritant Contact Dermatitis in fishermen in Padelegen Village, Pamekasan Regency. This study used an analytic observation method with a retrospective cross sectional approach. The research sample amounted to 32 people who were taken based on inclusion data and exclusion data. In this research the sampling technique was simple random sampling. The instruments used in this study were questionnaires, interviews, and documentation. Analysis of research results using ordinal logistic regression test. Based on the research that has been done, it can be concluded that the variables which influence the logistic results partially, is the service period with a sig value of 0.049, Personal Protective Equipment with a value of sig. 0.000 and personal hygiene 0.625. The results of the regression test simultaneously obtained results with a sig value of 0.044. So, it can be stated that there is an influence of internal factors on the incidence of Irritant Contact Dermatitis in fishermen in Padelegen Village, Pamekasan Regency. Advice for related agencies need to be held counseling or education about irritant contact dermatitis to fishermen in order to reduce the occurrence of occupational contact dermatitis. Keyword: Incidence Of Irritant Contact Dermatitis, Working Period, Personal Hygiene, PPE